The Link between Crude Palm Oil and Crude Oil Price in Various Periods of the Biodiesel Mandatory Policy in Indonesia - Nency Febrina Limbong; Alin Halimatussadiah (Department of Development Economics, Universitas Sriwijaya, 2022)
The biodiesel policy brought changes in the analysis of crude palm oil (CPO) prices. Supply and demand are no longer the main factors, but the correlation between CPO and crude oil prices. The main objective of this study is to provide an empirical study of the relationship between CPO and Indonesian Crude oil Price (ICP) in various periods of mandatory biodiesel policy in Indonesia. Using the Ordinary Least Square (OLS) method of time series data from 2001-2021, this study shows that in general CPO and ICP are positively and significantly correlated, but the price link is very dependent on the biodiesel policy that is implemented. ICP and CPO are positively and significantly correlated in the biodiesel mandatory period with limited subsidies (2006-2015) and in the biodiesel mandatory period with incentives which combined with progressive CPO export levies tariff (2020-2021). ICP and CPO are not correlated during the mandatory biodiesel period, combined with incentives and a fixed CPO export levy tariff (2016-2019). When CPO and ICP prices are strongly and significantly correlated, stock increases are not associated with a decrease in CPO prices. However, when the CPO and ICP prices are not significantly correlated, the stock increase is followed by a decrease in the CPO price. CPO price stabilization only occurs during the biodiesel mandatory period, combined with incentives and a fixed CPO export levy tariff.